Questionings about the value of words: violence and narratives (Tempo e Argumento, 2010)
This paper proposes to focus on the agressor’s speech acts, aiming at unveiling the meaning that the word ‘violence’ may have to the violence perpetrator. This study seeks to analyze the theoretical and epistemological problems that arise when attempting to document the memory of perpetrators, reflecting about the difficulties that arise when listening and interacting with those discourses. As the narratives exceed the theoretical categories and concepts available, this work attempts to build a better framework to analyze such discourses. This paper tries to examine the subjective position of the researcher in oral history, given the difficulties associated with that kind of interaction. These facts compel us to question whether ther should be a line separating the testimonies (that Primo Levi describes as a way of testifying the horror) from the confession (as a public performance of acknowledging or denying those crimes).
Keywords: violence; narratives; trauma; memory